2020
DOI: 10.1590/0001-3765202020191340
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 diabetes mellitus alters cardiac mitochondrial content and function in a non-obese mice model

Abstract: Type 2 diabetes mellitus (T2DM) is associated with an increase of premature appearance of several disorders such as cardiac complications. Thus, we test the hypothesis that a combination of a high fat diet (HFD) and low doses of streptozotocin (STZ) recapitulate a suitable mice model of T2DM to study the cardiac mitochondrial disturbances induced by this disease. Animals were divided in 2 groups: the T2DM group was given a HFD and injected with 2 low doses of STZ, while the CNTRL group was given a standard cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
(16 reference statements)
0
5
0
Order By: Relevance
“…Herein, we showed that feeding juvenile mice with HFD from weaning to adulthood, induce memory impairment and hippocampal dysfunction, as well as bioenergetic dysfunction in metabolic active tissues, leading to glucose intolerance, peripheral (BAT and liver) and central (hippocampus) mitochondrial dysfunction, despite not inducing overweight/obesity and changes in lipid profile. We used a combination of HFD with low STZ dose in order to increase the metabolic disturbance, consistent with high glucose levels and insulin resistance described elsewhere (Yurre et al, 2020). Similar dietary intervation starting from weaning also induced metabolic changes, such as dyslipidemia, hyperglycemia, and changes in leptin and insulin levels, in absence of obesity in juvenile mice (Boitard et al, 2012; Vinuesa et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Herein, we showed that feeding juvenile mice with HFD from weaning to adulthood, induce memory impairment and hippocampal dysfunction, as well as bioenergetic dysfunction in metabolic active tissues, leading to glucose intolerance, peripheral (BAT and liver) and central (hippocampus) mitochondrial dysfunction, despite not inducing overweight/obesity and changes in lipid profile. We used a combination of HFD with low STZ dose in order to increase the metabolic disturbance, consistent with high glucose levels and insulin resistance described elsewhere (Yurre et al, 2020). Similar dietary intervation starting from weaning also induced metabolic changes, such as dyslipidemia, hyperglycemia, and changes in leptin and insulin levels, in absence of obesity in juvenile mice (Boitard et al, 2012; Vinuesa et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, our data did not indicate any cardiac bioenergetic change in juvenile HFD mice. Adult mice submitted to same hyperglycemic-HFD model, presented changes in cardiac mitochondrial function after normalizing the O 2 consumption by the citrate synthase activity, a notable marker of mitochondrial content, suggesting that the cardiac bioenergetic alterations were associated with reduced mitochondrial content, not mitochondrial dysfunction (Yurre et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mice model of T2DM were induced by once daily Streptozotocin (STZ) 50 mg/kg by intraperitoneal injection (three continuous days) 15 . To induce insulin resistance, DM mice were fed with a high‐fat diet (D12492, Research Diets, New Brunswick, NJ, USA) during the study 16 . After 3 days of STZ administration, MI was induced surgically by chronic ligation of the left anterior descending coronary artery, as described previously 6 .…”
Section: Methodsmentioning
confidence: 99%
“… 15 To induce insulin resistance, DM mice were fed with a high‐fat diet (D12492, Research Diets, New Brunswick, NJ, USA) during the study. 16 After 3 days of STZ administration, MI was induced surgically by chronic ligation of the left anterior descending coronary artery, as described previously. 6 Mice in control group underwent sham‐operated surgery, but the left anterior descending coronary artery was not ligated.…”
Section: Methodsmentioning
confidence: 99%